Genetic engineering of baculovirus-insect cell system to improve protein production - Hong, Minqing; Li, Tingting; Xue, Wenhui; Zhang, Sibo; Cui, Lingyan; Wang, Hong; Zhang, Yuyun; Zhou, Lizhi; Gu, Ying; Xia, Ningshao; Li, Shaowei (Frontiers in Bioengineering and Biotechnology, 2022)
The Baculovirus Expression Vector System (BEVS), a mature foreign protein expression platform, has been available for decades, and has been effectively used in vaccine production, gene therapy, and a host of other applications. To date, eleven BEVS-derived products have been approved for use, including four human vaccines (Cervarix against cervical cancer caused by human papillomavirus [HPV], Flublok and Flublok Quadrivalent against seasonal influenza, Nuvaxovid/Covovax against COVID-19), two human therapeutics (Provenge against prostate cancer and Glybera against hereditary lipoprotein lipase deficiency [LPLD]) and five veterinary vaccines (Porcilis Pesti, BAYOVAC CSF E2, Circumvent PCV, Ingelvac CircoFLEX and Porcilis PCV). The BEVS has many advantages, including high safety, ease of operation and adaptable for serum-free culture. It also produces properly folded proteins with correct post-translational modifications, and can accommodate multi-gene– or large gene insertions. However, there remain some challenges with this system, including unstable expression and reduced levels of protein glycosylation. As the demand for biotechnology increases, there has been a concomitant effort into optimizing yield, stability and protein glycosylation through genetic engineering and the manipulation of baculovirus vector and host cells. In this review, we summarize the strategies and technological advances of BEVS in recent years and explore how this will be used to inform the further development and application of this system.